1989
DOI: 10.1111/j.1744-7348.1989.tb03395.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of sugar‐beet hypocotyl extension with potassium nitrate

Abstract: Steeping sugar-beet seeds in an aqueous thiram suspension, as now used commercially in the UK, makes seedling emergence more rapid and increases the number of plants established. This study investigated whether the potassium and nitrate, removed by steeping, were needed to stimulate subsequent hypocotyl growth. Experiments under controlled conditions showed that re-incorporation of KNO, by adding the salt to the steeping solution or, less wastefully during pelleting, slightly slowed root protrusion but made hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Both these alternatives could be adapted to leave the seed at a non-neutral pH if this would be beneficial . Yet another possibility might be to use nitric acid neutralised with potassium hydroxide and wash in such a way as to leave a small but beneficial residue of potassium nitrate [6]. In this study, it was assumed that thiram would have to be included to control Phoma betae .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both these alternatives could be adapted to leave the seed at a non-neutral pH if this would be beneficial . Yet another possibility might be to use nitric acid neutralised with potassium hydroxide and wash in such a way as to leave a small but beneficial residue of potassium nitrate [6]. In this study, it was assumed that thiram would have to be included to control Phoma betae .…”
Section: Discussionmentioning
confidence: 99%
“…Seed from each experiment was sown on fluted filter paper moistened with 2.6 ml 4 mM KNO 3 /g filter paper and incubated at about 8 °C, [ 12,6] . The proportion of seeds with a root at least 2 mm long (G) or with a hypocotyl over 2 cm tall (H) was recorded daily .…”
Section: Assessment Of Performancementioning
confidence: 99%
“…The influence of environmental conditions on germination and emergence has been thoroughly investigated, particularly in the case of sugar beet. But their specific effect on the first stages of seedling growth has received less attention, apart from works on fertilizer placement (Scott and Blair, 1988;Durrant and Mash, 1989) and the effect of aggregate size (Hammerton, 1961;Donald et al, 1987 The consequences of structure degradation of the soil surface were studied in plots sown in 1988, and given 0, 7, or 14 mm artificial rainfall just after sowing. Until the end of emergence, almost no crusting occured on plots without artificial rainfall because natural rainfall occured at low intensities.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction from the spring application was due mainly to the effects of Na and was most noticeable in dry years. More recent work by Durrant & Mash (1989) showed that steeping seed in KNO 3 solution could reduce the thermal time needed for hypocotyl growth. Radicle growth was always slowed even at small concentrations.…”
Section: Plant Population Densitymentioning
confidence: 99%